USING N-OVEL COATED SAND AS REACTIVE BED IN PERMEABLE BARRIER FOR ELIMINATION OF METHYL ORANGE DYE FROM GROUNDWATER* - Shihab, Ahmed H.; Faisal, Ayad A.H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study investigates the efficacy of sand coated with calcium / aluminum (Ca/Al)-layered double hydroxide (LDH) in the elimination of methyl orange dye from simulated groundwater using method of permeable reactive barrier. For green (sustainable) manufacturing of this sand, aluminum prepared from dissolution of alum (cheap coagulant) can be interacted chemically with calcium extracted from cement kiln dust byproduct to create nanoparticles of Ca and Al that precipitate on the filter sand. Sorption measurements for interaction of methyl orange dye and coated sand was well formulated by Langmuir model with highest value of correlation (determination coefficient= 0.999) and lowest errors (sum of squared errors= 0.0122). Also, the maximum capacity of adsorption was valued of 0.9453 mg/g and the sorption curve can classify as “favorable” type. According to desorption measurements, little percentage of dye (0.91%) can desorb from exhausted coated sand through washing with water due to strength of bonding between sorbent and dye molecules. Also, the exhausted sorbent can regenerate with efficiency not less than 85% after eight of regeneration cycles. Finally, measurements of breakthrough curves in the continuous mode operation using column setup proved that the propagation of dye front (and consequently the longevity of barrier) would increase significantly with thicker barrier and lowest values of influent concentration and flow rate. COMSOL (computer solution) package can use effectively in the simulation of these curves.